Structural Effects in the Addition–Fragmentation Reaction of Allylic Onium Salts - Tekin, Adem; Yurtsever, Mine; Yagci, Yusuf (Wiley, 2002)
Allylic onium salts with different hetero-atoms and various substituent groups at the allylic double bond have been shown to be very efficient initiators for cationic polymerization. When attacked by a radical, they become radical cations, which are highly unstable species, and undergo fragmentation into smaller radical cations called onium radical cations. The reaction mechanism involves radical formation, addition and fragmentation. In our previous work, radical initiators generated in the same way and under the same conditions are studied experimentally for their ability to affect the polymerization efficiency. Here, the factors affecting the polymerization efficiency are discussed theoretically using semi-empirical quantum mechanical techniques. The type of radical species, substituent group at the allylic side, the heteroatom at the onium side and the onium group itself are analyzed separately. For this purpose, the geometries of different onium radical cations to be fragmented are optimized and the strength of the C–heteroatom bond to be broken and the size of the radical cations after fragmentation are considered.
Keywords: Chemie